COVID-19 Risk Control and PPE use: Thai Personnel Safety - Chongchitpaisan, Wanna; Bandhukul, Adul (Biomedical Sciences and Clinical Medicine, 2025)
Objective: The study evaluated the COVID-19 risk control measures in hospitals and assessed the knowledge, attitudes, and practices of healthcare personnel regarding those measures with emphasis on promoting awareness and ensuring utilization of proper use of personal protective equipment (PPE) as urgent measures to safeguard healthcare personnel. Methods: This cross-sectional study assessed the perception of COVID-19 risk control measures based on the hierarchy of controls and examined the knowledge, attitudes, and adherence to safety measures among healthcare personnel using a structured questionnaire. Participants were selected based on their roles in patient care and occupational health management during the COVID-19 pandemic from 30 different Thai hospitals. Data analysis involved mean score comparison and examination of the magnitude of relationships using the Generalized Linear Model (GLMs). Results: A total of 3,086 healthcare personnel responded to this study, with 51.90% employed in regional and general hospitals. Among those personnel, 95.80% held a bachelor’s degree or lower and 44.50% were nurses, with 88.00% being responsible for patient care. The study found a high level of awareness regarding the health risk control measures implemented by the hospitals. Participants demonstrated high scores in knowledge, attitudes, and practices (KAP) related to the safety measures. Younger age, prior infection experience, higher knowledge scores, and positive perceptions of organizational PPE management were identified as factors associated with increased PPE adherence scores. Conclusion: PPE is an indispensable tool for protecting healthcare personnel from infectious hazards, particularly in environments where exposure to infectious patients is unavoidable. The effectiveness of PPE relies on comprehensive training, proper use and an adequate supply of PPE within the healthcare setting.